(3GdCfhGQ hGdbhGYO GdSfjI aj GdCSQGQ GdabgjIs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdTQjYI GdeYXeI GodeMeOjI RGO Gddg JYGdi efGQgG TQakG hYdhkG GTJedJ Ydi CUhd haQhY s
(3BNQgG (B:s
(3adjS eG aj GdMOjK ef gPG GdHGH hGddg CYde HGdUhGH ced GdcJGH MSH GdWGbI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMH hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(68) s
Keywords: (3Gdabg GdeGdcjs